2022
DOI: 10.5713/ab.21.0402
|View full text |Cite
|
Sign up to set email alerts
|

Effect of multi-enzymes supplementation on growth performance, meat quality, ileal digestibility, digestive enzyme activity and caecal microbiota in broilers fed low-metabolizable energy diet

Abstract: Objectives: This study was conducted to evaluate the effect of using low energy diet with multienzymes supplementation on different biological parameters in broilers.Methods: Three hundred Arbor Acres broiler chicks were randomly divided into three groups [Cont (Standard ME), L-ME (ME reduced by 50 kcal/kg without enzyme) and L-ME-MES (L-ME diet was supplemented with multi-enzymes)] with five replicates per group (20 chicks per replicate) at the start of second week. Grower and finisher diets were formulated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…The present results are also in accordance with those of several studies which reported that the relative weights of bursa and spleen for broilers were not significantly affected by multi-enzymes (Vahid et al, 2012;Metwally et al, 2020 andYaqoob et al, 2022) or probiotics supplemented (Sugiharto et al, 2018;Hidayat et al, 2020).…”
Section: Immune Organssupporting
confidence: 93%
See 3 more Smart Citations
“…The present results are also in accordance with those of several studies which reported that the relative weights of bursa and spleen for broilers were not significantly affected by multi-enzymes (Vahid et al, 2012;Metwally et al, 2020 andYaqoob et al, 2022) or probiotics supplemented (Sugiharto et al, 2018;Hidayat et al, 2020).…”
Section: Immune Organssupporting
confidence: 93%
“…Our findings agree with the findings of Midilli and Tuncer (2001), who reported that the best carcass and cut up yields were recorded for the enzymes and probiotics supplemented groups of broilers compared with their control. Similarly, Yaqoob et al, (2022) found that enzymes supplementation did not significantly affect liver, gizzard, heart and giblets percentages of broilers. Moreover, Hajati (2010) showed that enzyme supplementation to broiler ' s diet increased carcass, thighs drumsticks percentage significantly (P<0.05).…”
Section: Edible Partsmentioning
confidence: 91%
See 2 more Smart Citations
“…The endogenous enzymes of broiler chickens cannot adequately digest the dietary non-starch polysaccharides (NSP), and a high level of ingestion of these NSP by carbohydrases may exert anti-nutritional effects in broilers by increasing the digesta viscosity and decreasing the nutrient digestibility (Zeng et al, 2015). Exogenous enzymes are supplemented into corn-soya based poultry diets to reduce the effects of differing raw material quality, improve homogeneity and enhance nutrient digestibility (Yaqoob et al, 2022;Kutlu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%